Relationship between duration of type 2 diabetes mellitus and stress levels based on age, gender, anthropometry and vital signs - Thangavel, Dinesh; Pitchaipillai, Vijaiananth; Rangan, Venkatesan; Muthusamy, Anbarasi; Sivaprakasam, Raghuvaran (International Journal of Advances in Medicine, 2017)
Background: The incidence of diabetes mellitus is increasing at a rapid rate and by 2030 the case load would be doubled. Stress and various other factors such as physical and psychological factors play a significant role in the worsening of hyperglycemia in patients with type 2 diabetes mellitus. Aim and objective was to study the relationship between duration of type 2 diabetes mellitus and stress levels based on age, gender, anthropometry and vital signs. Methods: After obtaining approval from the institute ethics committee for human studies, the present study was conducted in the Department of Physiology, Dhanalakshmi Srinivasan Medical College and Hospital, Perambalur, Tamil Nadu on 50 type 2 diabetes mellitus patients (25 males, 25 females). After obtaining informed, written consent the following parameters such as duration of diabetes mellitus (Months), anthropometric parameters such as Body Mass Index (BMI), Waist Hip Ratio (WHR), Perceived Stress Scale (PSS) Scores, Vital signs viz. Pulse Rate (PR), Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP) and Respiratory Rate (RR) were recorded in all the study participants. Data for all the parameters was collected as per the study protocol and computerized in Microsoft excel database. All statistical analyses were done at 5% level of significance and P<0.05 was considered as statistically significant. Results: Average age of male and female volunteers was 52.16 ± 12.20 years and 55.68 ± 9.68 years respectively. Statistical analysis using independent Student’s ’t’ test, showed that there was no significant gender difference on the above mentioned parameters. Pearson’s correlation showed a statistically significant association between duration of diabetes mellitus and BMI (P<0.01). Correlation between duration of diabetes mellitus and PSS scores was also statistically significant (P=0.02). Conclusions: Results of the present study indicate that stress and increase in BMI are important independent risk factors for the worsening of hyperglycemia. When there is presence of other co morbid conditions the risk may be increased or it may affect the management or prognosis.